Age composition change and inter-provincial labor productivity: a study from the perspective of population dividend and population urbanization. Issue 1 (1st January 2020) - Fu, Liping; Wang, Yuhui; He, Lanping
ABSTRACT: Under the background of the aging social-transformation, studying the relationship between the change of age structure (CAS) and labor productivity (LP) was of great practical significance for sustainable development of China's economy. Therefore this paper first examined the overall impact of age structure changes on LP by the provincial panel data from year 2006 to 2015. Then regional difference was also carried out through the two dimensions of demographic dividend and population urbanization. Results showed that CAS with the increase of total dependency ratio and child dependency ratio had a significant negative impact on provincial LP. Increasing the labor input and accelerating the upgrading of human capital were the main lines to deal with the challenges of aging. From the perspective of demographic dividend and population urbanization, the impact of CAS on LP showed obvious inter-provincial and regional development differences.